Cryptosporidiosis outbreak in Amazonia, French Guiana, 2018 - Estelle Menu; Emilie Mosnier; Arnaud Cotrel; Loic Favennec; Romy Razakandrainibe; Stéphane Valot; Denis Blanchet; Frédéric Dalle; Damien Costa; Mélanie Gaillet; Magalie Demar; Franck de Laval (Public Library of Science (PLoS), 2022)
Background Cryptosporidiosis outbreaks in South America are poorly documented. In March 2018, 51 cases of cryptosporidiosis were reported in Maripasoula, a village located in a remote forest area along the border between Surinam and French Guiana. Method To identify the origin of the epidemic, we performed epidemiological, microbiological, and environmental investigations. Only the cases involving diarrhoea and Cryptosporidium-positive stool were considered as bona fide, while cases involving diarrhoea and close contact with a confirmed case were classified as "possible". Results We identified 16 confirmed cases and 35 possible ones. Confirmed cases comprised nine children (median age of 18 months, range: 6-21), one immunocompromised adult and six soldiers. One child required a hospitalisation for rehydration. All 16 Cryptosporidium stools were PCR positive, and sequencing of the gp60 gene confirmed only one Cryptosporidium hominis subtype IbA10G2. Tap water consumption was the only common risk factor identified. Contamination of the water network with Cryptosporidium parvum subtype IIdA19G2 was found. Conclusion Water quality is a major public health issue in Amazonian French Guiana, especially for population at risk (children, people with comorbidity, travelers). For them, alternative water supply or treatment should be implemented.